Balnearios y manantiales del pirineo aragonés a través de los viajeros - Armijo Castro, Francisco (Anales de Hidrología Médica, 2007)
The Aragon Pyrenees, due to the magnitude of its mountains, has been one of the less visited areas in Spain. In general, this area is an important reservoir of many types of waters used as healing agents, mineral medicinal waters or just for domestic use of the people living there. In this paper we ask for the travellers’ opinion on the spas and springs that they found on their way through the Pyrenees.
Keywords: Mineral medicinal water; Spas; Springs; Pyrenees; Aragón; Travellers; 12th-20th centuries history